Hunger [videorecording (DVD)] - McQueen, Steve, 1969-; McQueen, Steve, 1969-; Fassbender, Michael, 1977-; Cunningham, Liam; Graham, Stuart, 1967- (Criterion collection, 2009)
In Northern Ireland's Maze prison in 1981, 27-year-old Irish Republican Army member Bobby Sands went on a hunger strike to protest the British government's refusal to recognize him and his fellow IRA inmates as political prisoners. A transcendent depiction of what a human being is willing to endure in order to be heard.